Optimization of the DTC control for doubly-fed induction motor using a PID based-genetic algorithm: Experimental validation on the dSPACE 1104 board - Ech-Chaouy Houssam; Derouich Aziz; Mahfoud Said (E3S Web of Conferences)
This article presents a very interesting approach to Direct Torque Control (DTC) for a doubly-fed induction motor utilizing two voltage-source inverters. The speed control of this system is achieved using a proportional-integral-derivative (PID) controller optimized by a genetic algorithm. Although the conventional DTC method offers many advantages, such as effective and dynamic control, robustness, ease of use, and impressive results, it also has drawbacks, including fluctuations in electromagnetic torque and variable switching frequencies, which lead to vibrations and accelerated aging of the machine. The purpose of this article is to improve torque control based on the direct method (DTC) and to address these limitations. To achieve this, a new control strategy called Genetic Algorithm-based DTC (GA-DTC) is proposed. This strategy integrates the optimized PID controller and is implemented across the entire operational range of the system. The entire system is validated using the MATLAB/Simulink environment to analyze the machine’s characteristics, its transient behavior, and its performance in steady state. This integration leads to a notable improvement in the machine’s performance, particularly in tracking speed and torque set points, reducing response times, and decreasing overshoot. Experimental validation is carried out using a 1.5 kW rotating electrical machine (DFIM-DCM) connected to a resistive load. The experiments are conducted using the DSPACE DS1104 experimental system, and the system’s behavior is tested under various operating conditions. The results obtained show the evolution of speed, torque, as well as stator and rotor currents. According to these results, the motor’s performance has been improved: response time has decreased, settling time has increased, and torque ripple has been reduced.